Composite material for ship propulsion system and preparation method thereof
By using a combination of ultra-high molecular weight polyethylene and ionic liquid grafting MXenes, a composite material suitable for ship propulsion systems was prepared, which solved the friction and wear problems of water-lubricated tail bearings under working conditions, and achieved a low coefficient of friction and a small wear rate.
Patent Information
- Application Number
- CN202310323803.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-03-30
AI Technical Summary
The tail bearings of the existing water-lubricated ship propulsion system have a large water film thickness under the same working conditions and insufficient design specific pressure, which leads to serious friction and wear, threatening the safety of ship operations.
Using a composite material, including ultra-high molecular weight polyethylene, perfluoropolyether acrylate copolymer, ethylene-octene copolymer elastomer, nitrile rubber and ionic liquid grafting MXenes, pelletized through a twin screw extrusion mechanism, and pressurized and insulated in the mold to improve the performance of the material.
The composite material exhibits a low coefficient of friction and a small volume wear rate under dry friction and water lubrication conditions, which can effectively reduce friction and wear, and is suitable for water-lubricated stern bearings in marine propulsion systems.
Smart Images

Figure BDA0004152621910000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, in particular to a composite material for a ship propulsion system and a preparation method thereof. Background Art
[0002] Nowadays, the stern bearings of ship propulsion systems are lubricated by oil or water. The stern tube of oil-lubricated bearings is filled with lubricating oil, and two stern tube sealing devices are required. The stern bearings are mostly made of white alloy, which has low friction loss. Currently, most commercial ships use this type. However, if a collision or grounding accident causes damage to the stern tube or the sealing device fails and leaks oil, the shaft system must stop running and be repaired in the dock, which will also cause a certain degree of marine pollution. The stern tube of water-lubricated bearings is filled with water and flows, and only the front sealing device is required.
[0003] As an alternative, water-lubricated bearings made of polymer materials are widely used in military and civilian ships. However, under the same working conditions, the thickness of the water film formed in the water-lubricated bearing is only 1 / 8 of the oil film, and the design specific pressure under the same conditions can only reach 1 / 3 of the oil-lubricated bearing, which makes it difficult to achieve a good fluid dynamic lubrication state, resulting in severe friction and wear, causing seal failure, and seriously threatening the safe operation of ships. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a composite material for a ship propulsion system and a preparation method thereof.
[0005] The technical solutions adopted are as follows:
[0006] A composite material for a ship propulsion system, comprising the following components by weight:
[0007] 45-60 parts of ultra-high molecular weight polyethylene, 5-10 parts of perfluoropolyether acrylate copolymer, 10-15 parts of ethylene-octene copolymer elastomer, 3-5 parts of nitrile rubber, and 4-8 parts of ionic liquid grafted MXenes.
[0008] Furthermore, the following components are included by weight:
[0009] 55 parts of ultra-high molecular weight polyethylene, 8 parts of perfluoropolyether acrylate copolymer, 12 parts of ethylene-octene copolymer elastomer, 4 parts of nitrile rubber, and 6 parts of ionic liquid grafted MXenes.
[0010] Furthermore, the preparation method of the perfluoropolyether acrylate copolymer is as follows:
[0011] Acrylic acid is neutralized with NaOH solution, and then methyl methacrylate, butyl acrylate, glycidyl methacrylate and perfluoropolyether methacrylate are added and stirred to obtain a mixed monomer solution. Cyclohexane and a dispersant are mixed and stirred thoroughly, nitrogen is introduced for deoxygenation, the temperature is raised to 45-55°C, the mixed monomer solution is slowly added, and the mixture is mixed under continuous stirring to form a stable reverse phase suspension. Then sodium persulfate solution is added dropwise, and the mixture is reacted at 70-80°C for 2-4h after the addition is completed. After the reaction is completed, the mixture is cooled to room temperature, the upper oil phase is poured out, and the solid product is washed with methanol for several times and then dried in vacuo.
[0012] Further, the degree of neutralization is 55-63%.
[0013] Furthermore, the mass ratio of acrylic acid, methyl methacrylate, butyl acrylate, glycidyl methacrylate, and perfluoropolyether methacrylate is 5-10:1-2:2-4:0.5-1:0.5-1.
[0014] Furthermore, the ionic liquid grafted MXenes are ionic liquid grafted two-dimensional transition metal carbides.
[0015] Furthermore, the ionic liquid is an imidazole ionic liquid containing a double bond.
[0016] Furthermore, the two-dimensional transition metal carbide is Ti2CT X or Ti3C2T X .
[0017] Furthermore, the preparation method of the ionic liquid grafted two-dimensional transition metal carbide is as follows:
[0018] After mixing ethanol and water, adjust the pH to 3-4 with hydrochloric acid, add silane coupling agent, stir evenly, and let stand for 4-6 hours, add two-dimensional transition metal carbide, heat to 60-70°C, react for 4-6 hours, filter, and vacuum dry to obtain modified two-dimensional transition metal carbide, mix ionic liquid with ethanol and water, then add modified two-dimensional transition metal carbide and azobisisobutyronitrile, under nitrogen protection, stir and heat to 75-85°C, react for 18-24 hours, filter the reaction solution, wash the product with ethanol, and vacuum dry to constant weight.
[0019] The present invention also provides a method for preparing a composite material for a ship propulsion system:
[0020] Ultra-high molecular weight polyethylene, perfluoropolyether acrylate copolymer, ethylene-octene copolymer elastomer, nitrile rubber, and ionic liquid grafted MXenes are dried and fully mixed. The resulting mixture is added to a twin-screw extruder, heated and melted, and then extruded into granules. The resulting granules are transferred to a mold, first pressurized to 10-15MPa, maintained for 10-15min, then heated to 170-190℃, maintained for 20-30min, then pressurized to 18-20MPa, maintained for 1-5min, restored to normal pressure, naturally cooled to 40-50℃, demolded, and trimmed.
[0021] Beneficial effects of the present invention:
[0022] The present invention provides a composite material for a ship propulsion system. Ultra-high molecular weight polyethylene has incomparable impact resistance, wear resistance, self-lubrication and chemical corrosion resistance properties that other plastics cannot match due to its high relative molecular weight. Ethylene-octene copolymer elastomer has a low relative molecular weight and good fluidity, and can be evenly dispersed in ultra-high molecular weight polyethylene. After being added, it can not only play a reinforcing effect, but also reduce melt viscosity and improve processing fluidity. Perfluoropolyether acrylate copolymer has good compatibility with ultra-high molecular weight polyethylene and has low surface energy. During processing, it can reduce the internal friction of resin molecules, increase the melting rate and the deformability of the melt, reduce the apparent viscosity of the melt, and improve the overall plasticization effect. MXenes has a high specific gravity of graphene. The characteristics of surface area and high conductivity, as well as the advantages of flexible and adjustable components and controllable minimum nanolayer thickness, have shown great potential in the fields of energy storage, adsorption, sensors, conductive fillers, etc., but there is no report on its application in wear-resistant materials. The inventor modified it with a coupling agent and then grafted it with ionic liquid through double bond polymerization. During the friction process, part of the ionic liquid migrated to the surface of the material and formed a lubricating film with water molecules, providing boundary lubrication for the friction process, thereby reducing the friction coefficient and wear. After testing, the composite material prepared by the present invention has a lower dry friction coefficient and wet friction coefficient under water lubrication conditions, and a small volume wear rate, and can be suitable for water-lubricated stern bearings of ship propulsion systems. DETAILED DESCRIPTION
[0023] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The technologies not mentioned in the present invention are all referenced to the prior art.
[0024] Embodiment 1:
[0025] A composite material for a ship propulsion system, comprising the following components by weight:
[0026] 55 parts of ultra-high molecular weight polyethylene, 8 parts of perfluoropolyether acrylate copolymer, 12 parts of ethylene-octene copolymer elastomer, 4 parts of nitrile rubber, and 6 parts of ionic liquid grafted MXenes.
[0027] Wherein, the preparation method of perfluoropolyether acrylate copolymer is as follows:
[0028] 80g of acrylic acid was neutralized with 10% by mass NaOH solution to a neutralization degree of 63%, and then 15g of methyl methacrylate, 30g of butyl acrylate, 10g of glycidyl methacrylate and 5g of perfluoropolyether methacrylate were added and stirred to obtain a mixed monomer solution. 200mL of cyclohexane and 9g of dispersant (Span-80 and Tween-80 in a mass ratio of 1:1) were mixed and stirred thoroughly, nitrogen was introduced for deoxygenation, the temperature was raised to 50°C, the mixed monomer solution was slowly added, and the mixture was mixed under continuous stirring to form a stable reverse phase suspension, and then 10mL of 10% by mass sodium persulfate solution was dropped, and the mixture was reacted at 75°C for 4h after the dropwise addition. After the reaction was completed, the mixture was cooled to room temperature, the upper oil phase was poured out, the solid product was washed with methanol several times, and then vacuum dried at 50°C for 18h.
[0029] Ionic liquid grafted MXenes are double bond-containing imidazole ionic liquid grafted Ti2CT X , the preparation method is as follows:
[0030] Mix 500 mL of ethanol and 100 mL of water, adjust the pH to 3-4 with hydrochloric acid, add 20 g of silane coupling agent KH-570, stir evenly, let stand for 5 hours, and then add 100 g of Ti2CT X The temperature was raised to 65 °C for 6 h, then filtered and dried at 50 °C in vacuum for 18 h to obtain modified Ti2CT X , 20g 1-allyl-3-methylimidazole chloride was mixed with 400mL ethanol and 50mL water, and then the modified Ti2CT X And 0.85g of azobisisobutyronitrile was added, and under nitrogen protection, the temperature was raised to 80°C with stirring for 24h. The reaction liquid was filtered, and the obtained product was washed with ethanol and dried at 50°C in vacuum until constant weight.
[0031] The preparation method of the composite material for the ship propulsion system is as follows:
[0032] Ultra-high molecular weight polyethylene, perfluoropolyether acrylate copolymer, ethylene-octene copolymer elastomer, nitrile rubber, and ionic liquid grafted MXenes were dried and fully mixed. The resulting mixture was added to a twin-screw extruder, heated and melted, and then extruded into granules. The resulting granules were transferred to a mold, first pressurized to 12 MPa, maintained for 15 minutes, then heated to 180°C, maintained for 25 minutes, and then pressurized to 20 MPa. After maintaining the temperature for 5 minutes, the pressure was restored to normal and the temperature was naturally lowered to 45°C, and the mold was demolded and trimmed.
[0033] Embodiment 2:
[0034] A composite material for a ship propulsion system, comprising the following components by weight:
[0035] 60 parts of ultra-high molecular weight polyethylene, 10 parts of perfluoropolyether acrylate copolymer, 15 parts of ethylene-octene copolymer elastomer, 3 parts of nitrile rubber, and 8 parts of ionic liquid grafted MXenes.
[0036] Wherein, the preparation method of perfluoropolyether acrylate copolymer and ionic liquid grafted MXenes is the same as that of Example 1;
[0037] The preparation method of the composite material for the ship propulsion system is as follows:
[0038] Ultra-high molecular weight polyethylene, perfluoropolyether acrylate copolymer, ethylene-octene copolymer elastomer, nitrile rubber, and ionic liquid grafted MXenes were dried and fully mixed. The resulting mixture was added to a twin-screw extruder, heated and melted, and then extruded into granules. The resulting granules were transferred to a mold, first pressurized to 15 MPa, maintained at pressure for 15 minutes, then heated to 190°C, maintained at temperature for 30 minutes, and then pressurized to 20 MPa. After maintaining temperature for 5 minutes, the pressure was restored to normal and the temperature was naturally lowered to 50°C, and the mold was demolded and trimmed.
[0039] Embodiment 3:
[0040] A composite material for a ship propulsion system, comprising the following components by weight:
[0041] 45 parts of ultra-high molecular weight polyethylene, 5 parts of perfluoropolyether acrylate copolymer, 10 parts of ethylene-octene copolymer elastomer, 3 parts of nitrile rubber, and 4 parts of ionic liquid grafted MXenes.
[0042] Wherein, the preparation method of perfluoropolyether acrylate copolymer and ionic liquid grafted MXenes is the same as that of Example 1;
[0043] The preparation method of the composite material for the ship propulsion system is as follows:
[0044] Ultra-high molecular weight polyethylene, perfluoropolyether acrylate copolymer, ethylene-octene copolymer elastomer, nitrile rubber, and ionic liquid grafted MXenes were dried and fully mixed. The resulting mixture was added to a twin-screw extruder, heated and melted, and then extruded into granules. The resulting granules were transferred to a mold, first pressurized to 10 MPa, maintained for 10 minutes, then heated to 170°C, maintained for 20 minutes, and then pressurized to 18 MPa. After maintaining the pressure for 1 minute, the pressure was restored to normal and the temperature was naturally lowered to 40°C, and the mold was demolded and trimmed.
[0045] Embodiment 4:
[0046] A composite material for a ship propulsion system, comprising the following components by weight:
[0047] 60 parts of ultra-high molecular weight polyethylene, 5 parts of perfluoropolyether acrylate copolymer, 15 parts of ethylene-octene copolymer elastomer, 5 parts of nitrile rubber, and 4 parts of ionic liquid grafted MXenes.
[0048] Wherein, the preparation method of perfluoropolyether acrylate copolymer and ionic liquid grafted MXenes is the same as that of Example 1;
[0049] The preparation method of the composite material for the ship propulsion system is as follows:
[0050] Ultra-high molecular weight polyethylene, perfluoropolyether acrylate copolymer, ethylene-octene copolymer elastomer, nitrile rubber, and ionic liquid grafted MXenes are dried and fully mixed. The resulting mixture is added to a twin-screw extruder, heated and melted, and then extruded into granules. The resulting granules are transferred to a mold, first pressurized to 15 MPa, maintained at pressure for 10 minutes, then heated to 190°C, maintained at temperature for 20 minutes, and then pressurized to 20 MPa. After maintaining temperature for 1 minute, the pressure is restored to normal and the temperature is naturally lowered to 50°C, and the mold is demolded and trimmed.
[0051] Embodiment 5:
[0052] A composite material for a ship propulsion system, comprising the following components by weight:
[0053] 45 parts of ultra-high molecular weight polyethylene, 10 parts of perfluoropolyether acrylate copolymer, 10 parts of ethylene-octene copolymer elastomer, 4 parts of nitrile rubber, and 8 parts of ionic liquid grafted MXenes.
[0054] Wherein, the preparation method of perfluoropolyether acrylate copolymer and ionic liquid grafted MXenes is the same as that of Example 1;
[0055] The preparation method of the composite material for the ship propulsion system is as follows:
[0056] Ultra-high molecular weight polyethylene, perfluoropolyether acrylate copolymer, ethylene-octene copolymer elastomer, nitrile rubber, and ionic liquid grafted MXenes were dried and fully mixed. The resulting mixture was added to a twin-screw extruder, heated and melted, and then extruded into granules. The resulting granules were transferred to a mold, first pressurized to 10 MPa, maintained at pressure for 15 minutes, then heated to 170°C, maintained at temperature for 30 minutes, and then pressurized to 18 MPa. After maintaining temperature for 5 minutes, the pressure was restored to normal and the temperature was naturally lowered to 40°C, and the mold was demolded and trimmed.
[0057] Comparative Example 1:
[0058] The method is substantially the same as Example 1, except that no perfluoropolyether acrylate copolymer is added.
[0059] Comparative Example 2:
[0060] The method is substantially the same as Example 1, except that no ethylene-octene copolymer elastomer is added.
[0061] Comparative Example 3:
[0062] It is basically the same as Example 1, except that no ionic liquid is added to graft MXenes.
[0063] Comparative Example 4:
[0064] It is basically the same as Example 1, except that MXenes are directly added without ionic liquid grafting.
[0065] Performance Test:
[0066] The composite materials prepared in Examples 1-5 of the present invention and Comparative Examples 1-4 were used as samples;
[0067] The standard ring block specimen is used: the outer diameter is 50mm, the inner diameter is 40mm, and the thickness is 8mm. The corresponding friction pair material is tin bronze ZQSn 10 Zn2, the test was conducted on a universal wear testing machine;
[0068] The performance tests include dry friction test, wear test and water-lubricated friction test and wear test. The dry friction coefficient refers to the friction coefficient measured without lubricating medium. The water-lubricated friction coefficient refers to the friction coefficient measured with water as lubricating medium. Friction test conditions: GB / T 3960-2016, loading force 196N, loading rate 200r / min, volume wear rate is calculated as V=(m1-m2) / ρ, wear test conditions: GB / T 3960-2016, loading force 196N, loading rate 200r / min, where m1 is the sample mass before the experiment, m2 is the sample mass after the experiment, and ρ is the sample density.
[0069] The test results are shown in Table 1 below:
[0070] Table 1:
[0071]
[0072] It can be seen from Table 1 above that the composite material prepared by the present invention has a lower dry friction coefficient and a lower wet friction coefficient under water lubrication conditions, a small volume wear rate, and can be applied to water-lubricated stern bearings of ship propulsion systems.
[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite material for a ship propulsion system, characterized in that: The composition is calculated by weight: 45-60 parts of ultra-high molecular weight polyethylene, 5-10 parts of perfluoropolyether acrylate copolymer, 10-15 parts of ethylene-octene copolymer elastomer, 3-5 parts of nitrile rubber, 4-8 parts of ionic liquid grafted MXenes; The preparation method of the perfluoropolyether acrylate copolymer is as follows: Neutralize acrylic acid with NaOH solution to a neutralization degree of 55-63%, then add methyl methacrylate, butyl acrylate, glycidyl methacrylate, and perfluoropolyether methacrylate, mix and stir evenly to obtain a mixed monomer solution, mix cyclohexane and a dispersant and stir thoroughly, introduce nitrogen to deoxygenate, heat to 45-55° C., slowly add the mixed monomer solution, mix under continuous stirring to form a stable reverse phase suspension, then drop sodium persulfate solution, react at 70-80° C. for 2-4 hours after the dropwise addition, cool to room temperature after the reaction is completed, pour out the upper oil phase, wash the solid product with methanol several times, and then vacuum dry it; The mass ratio of acrylic acid, methyl methacrylate, butyl acrylate, glycidyl methacrylate, and perfluoropolyether methacrylate is 5-10:1-2:2-4:0.5-1:0.5-1; The ionic liquid grafted MXenes is an ionic liquid grafted two-dimensional transition metal carbide, and the two-dimensional transition metal carbide is Ti2CT X or Ti3C2T X , the ionic liquid is an imidazole ionic liquid containing a double bond; The preparation method of the ionic liquid grafted two-dimensional transition metal carbide is as follows: After mixing ethanol and water, adjust the pH to 3-4 with hydrochloric acid, add silane coupling agent KH-570, stir evenly and let stand for 4-6 hours, add two-dimensional transition metal carbide, heat to 60-70°C and react for 4-6 hours, filter and vacuum dry to obtain modified two-dimensional transition metal carbide, mix ionic liquid with ethanol and water, then add modified two-dimensional transition metal carbide and azobisisobutyronitrile, under nitrogen protection, stir and heat to 75-85°C and react for 18-24 hours, filter the reaction solution, wash the product with ethanol and vacuum dry to constant weight.
2. The composite material for a ship propulsion system according to claim 1, characterized in that: The composition is calculated by weight: 55 parts of ultra-high molecular weight polyethylene, 8 parts of perfluoropolyether acrylate copolymer, 12 parts of ethylene-octene copolymer elastomer, 4 parts of nitrile rubber, and 6 parts of ionic liquid grafted MXenes.
3. A method for preparing a composite material for a ship propulsion system according to any one of claims 1 to 2, characterized in that: Ultra-high molecular weight polyethylene, perfluoropolyether acrylate copolymer, ethylene-octene copolymer elastomer, nitrile rubber, and ionic liquid grafted MXenes are dried and fully mixed. The resulting mixture is added to a twin-screw extruder, heated and melted, and then extruded into granules. The resulting granules are transferred to a mold, first pressurized to 10-15MPa, maintained for 10-15min, then heated to 170-190℃, maintained for 20-30min, then pressurized to 18-20MPa, maintained for 1-5min, restored to normal pressure, naturally cooled to 40-50℃, demolded, and trimmed.
Citation Information
Patent Citations
Fluorosilicone acrylate emulsion and preparing method of fluorosilicone acrylate emulsion
CN104804148A
Mxene-based flame-retardant unsaturated resin material and preparation method thereof
CN113717511A